Designing tasks to promote interaction (2002)
Four tasks, set up by an English teacher in his EFL lessons with undergraduate Licenciatura students, were analyzed and compared on the basis of the input involved while they were being developed. The nature of input was established for each case through observing particular features of each task as well as factors that might affect input in those. At the end, it was seen how tasks play an essential role in the way participants make an effort to understand and be understood in their interactions.